ThorSim: Throughput-Oriented Timing Simulation of FinFET Digital Circuits - Reimer, Jan Dennis; Holst, Stefan; Sadeghi-Kohan, Somayeh; Wunderlich, Hans-Joachim; Hellebrand, Sybille (IEEE International Symposium of Electronics Design Automation (ISEDA'25), May 2025)

Time-resolved momentum microscopy with fs-XUV photons at high repetition rates with flexible energy and time resolution - Schiller, Karl Jakob; Sternemann, Lasse; Stupar, Matija; Omar, Alan; Hoffmann, Martin; Nitschke, Jonah Elias; Mischke, Valentin; Janas, David Maximilian; Ponzoni, Stefano; Zamborlini, Giovanni; Saraceno, Clara Jody; Cinchetti, Mirko (Scientific Reports)
Abstract Time-resolved momentum microscopy is an emerging technique based on photoelectron spectroscopy for characterizing ultrafast electron dynamics and the out-of-equilibrium electronic structure of materials in the entire Brillouin zone with high efficiency. In this article, we introduce a setup for time-resolved momentum microscopy based on an energy-filtered momentum microscope coupled to a custom-made high-harmonic generation photon source driven by a multi-100 kHz commercial Yb-ultrafast laser that delivers fs pulses in the extreme ultraviolet range. The laser setup includes a nonlinear pulse compression stage employing spectral broadening in a Herriott-type bulk-based multi-pass cell. This element allows flexible tuning of the driving pulse duration, providing a versatile time-resolved momentum microscopy setup featuring two operational modes designed to enhance either the energy or time resolution. We show the capabilities of the system by tracing ultrafast electron dynamics in the conduction band valleys of a bulk crystal of the 2D semiconductor WS 2 . Using uncompressed driving laser pulses, we demonstrate an energy resolution better than (107 ± 2) meV, while compressed pulses lead to a time resolution better than (48.8 ± 17) fs.

Tracing the ultrafast buildup and decay of d-d transitions in FePS3 - Nitschke, Jonah Elias; Sternemann, Lasse; Gutnikov, Michael; Schiller, Karl; Coronado, Eugenio; Omar, Alan; Zamborlini, Giovanni; Saraceno, Clara; Stupar, Matija; Ruiz, Alberto M.; Esteras, Dorye L.; Baldoví, José J.; et al. (Newton)

Gestärkt durchs Studium - Universitäre Unterstützungsangebote zum Stress- und Selbstmanagement - Bobe, Julia; Decker, Claudia; Klingsieck, Katrin B.

The Role of Subjective Discomfort in Procrastination - Feeling bad about unnecessary delaying and therefore, preventing it? - Bobe, Julia; Klingsieck, Katrin B.

Analyzing performance portability for a SYCL implementation of the 2D shallow water equations - Büttner, Markus; Alt, Christoph; Kenter, Tobias; Köstler, Harald; Plessl, Christian; Aizinger, Vadym (The Journal of Supercomputing)
SYCL is an open standard for targeting heterogeneous hardware from C++. In this work, we evaluate a SYCL implementation for a discontinuous Galerkin discretization of the 2D shallow water equations targeting CPUs, GPUs, and also FPGAs. The discretization uses polynomial orders zero to two on unstructured triangular meshes. Separating memory accesses from the numerical code allow us to optimize data accesses for the target architecture. A performance analysis shows good portability across x86 and ARM CPUs, GPUs from different vendors, and even two variants of Intel Stratix 10 FPGAs. Measuring the energy to solution shows that GPUs yield an up to 10x higher energy efficiency in terms of degrees of freedom per joule compared to CPUs. With custom designed caches, FPGAs offer a meaningful complement to the other architectures with particularly good computational performance on smaller meshes. FPGAs with High Bandwidth Memory are less affected by bandwidth issues and have similar energy efficiency as latest generation CPUs.

Evaluating oneAPI I/O Pipes in a Case Study of Scaling a SYCL Jacobi Solver to multiple FPGAs - Alt, Christoph; Plessl, Christian; Kenter, Tobias (Proceedings of the 13th International Workshop on OpenCL and SYCL)
In the context of high-performance computing (HPC) for distributed workloads, individual field-programmable gate arrays (FPGAs) need efficient ways to exchange data, which requires network infrastructure and software abstractions. Dedicated multi-FPGA clusters provide inter-FPGA networks for direct device to device communication. The oneAPI high-level synthesis toolchain offers I/O pipes to allow user kernels to interact with the networking ports of the FPGA board. In this work, we evaluate using oneAPI I/O pipes for direct FPGA-to-FPGA communication by scaling a SYCL implementation of a Jacobi solver on up to 25 FPGAs in the Noctua 2 cluster. We see good results in weak and strong scaling experiments.
Keywords: Multi-FPGA; High-level Synthesis; oneAPI; FPGA

Adaptive Spectral Block Floating Point for Discontinuous Galerkin Methods - Sundriyal, Shivam; Büttner, Markus; Alt, Christoph; Kenter, Tobias; Aizinger, Vadym (2025 IEEE High Performance Extreme Computing Conference (HPEC))

Turning to Online Forums for Legal Information: A Case Study of GDPR’s Legitimate Interests - Kyi, Lin; Santos, Cristiana; Ammanaghatta Shivakumar, Sushil; Roesner, Franziska; Biega, Asia (Lecture Notes in Computer Science)

Why Engineering Students Choose a Career in Teacher Education – Qualitative Analysis of Bachelor Students' Motives - Vernholz, Mats; Temmen, Katrin (Towards inclusive and egalitarian vocational education and training: Key challenges and strategies from a holistic and multi-contextual approach. Proceedings of the 6th Crossing Boundaries Conference in Vocational Education and Training)

Section 39 (Digital Markets Act) - Bartlitz, David; Gräfe, Alexander (Handbuch des EU-Wirtschaftsrechts)

Diskussionsbeitrag zu Klimaquote, Klimagovernance und Rechtsformzusatz "klimaneutral" - Bartlitz, David (Verhandlungen des 74. Deutschen Juristentages Stuttgart 2024)

Reformation mit Hanns Dieter Hüsch feiern 31. Oktober 2025

How does practice modulate fake-production costs in a basketball task? Analyses of frequency distributions and mixture effects - Böer, Nils Tobias; Schütz, Christoph; Weigelt, Matthias; Güldenpenning, Iris (Psychological Research)
Abstract The execution of incompatible actions imposes costs on action planning, commonly known as response-response incompatibility-costs. This phenomenon is also evident in sports: A basketball player who performs a pass in one direction whilst orienting the head into the contrary direction (pass with head fake) needs more time to initiate the action as if pass direction and head orientation are the same (pass without head fake). The aim of this study was twofold: First, we present a re-analysis of the data from Böer et al. (Psychological Research 88:523–524, 2024) using mixture effect modelling (Miller, Behavior Research Methods 38:92–106, 2006) explore if fake-production costs manifest continuously (uniform effect) in all participants or if some participants show fake-production costs occasionally but substantially (mixed effect). Second, we collected data of a control group which was analysed with the previous data of the practice group and fitted initiation times (ITs) to an ex-Gaussian distribution. The analysis of mixture effects revealed that most participants exhibited a uniform effect when they didn’t have time to mentally prepare the movement. This pattern was not changed by practice, suggesting fake-production costs can’t be overcome by practice alone without mental preparation time. The analysis of mean ITs revealed improvements in the practice group but not in the control group, independent of the type of pass performed. The distribution analyses complemented these findings as it showed that the improvement in participants’ performance with increasing practice can mainly be attributed to a reduction of the exponential part of the distribution (parameter tau).
Keywords: Sport Psychology; Sport Science; Deception; Distribution Analysis

The mere presence of a social partner modulates fake-production costs - Böer, Nils Tobias; Güldenpenning, Iris; Weigelt, Matthias (57th Herbsttreffen der experimentellen Kognitionspsychologie (HExKoP))
Keywords: Deception; Sport Psychology; Social Interaction

Erfolgreich Studieren – sinnvolle Lernstrategien erlernen - Nölle, Florian; Schmid, Hans-Joachim (Tag der Lehre 2025)

Overcoming disciplinary cultures as innovation barriers: realising transfer potentials - Sloane, Hannah Sabrina

Listening to students' voices: Engaged pedagogy as a pathway to pedagogical possibilities. - Lin-Januszewski, Liang-Wen (Sociology)
This study explores undergraduate sociology students’ perceptions of conventional pedagogical practices and their aspirations for an ideal learning environment at a regional German university. Drawing on semi-structured interviews with 41 students enrolled between 2021 and 2023, the research investigates how students envision the study of sociology and their preferences for pedagogical approaches. The findings reveal that students’ diverse visions converge on common themes aligning with engaged pedagogy and critical pedagogy principles. Students express a desire for learning environments that challenge existing forms of domination, promote active knowledge acquisition, and foster mutual respect. They seek meaningful knowledge that connects theory to practice, facilitates personal growth, and empowers them to effect social change. The study contributes to ongoing debates about pedagogical practices in higher education, especially in sociology, by providing empirical evidence of students’ subjective experiences and desires, emphasising the need for engaged pedagogy that nurtures holistic development and values students’ agency.
Keywords: bell hooks; critical pedagogy; engaged pedagogy; pedagogy of sociology; student voices

NL2LS: LLM-based Automatic Linking of Knowledge Graphs - Ihtassine, Reda; Firmansyah, Asep Fajar; Srivastava, Nikit; Ali, Manzoor; Ngonga Ngomo, Axel-Cyrille; Sherif, Mohamed (Proceedings of the 12th Knowledge Capture Conference 2025, K-CAP 2025, The Thirteenth International Conference on Knowledge Capture, December 10 - 12, 2025, Dayton, Ohio, USA)
Keywords: Srivastava ali dice enexa firmansyah ihtassine ngonga sailproject sherif whale

Promoting women researchers in STEM: The case of German higher education. - Chang, Chen-Wei; Lin-Januszewski, Liang-Wen (Towards a gender-inclusive future: National strategies for cultivating women researchers in STEM)